Inhibition of interleukin‐12 and/or interleukin‐23 for the treatment of psoriasis: What is the evidence for an effect on malignancy? - Ergen, Elizabeth N. (Exp Dermatol, 2018)
Immune cells and cytokines play an important role in the pathogenesis of psoriasis. Interleukin‐12 (IL‐12) and IL‐23 promote cellular responses mediated by T cells, which contribute to an inflammatory loop responsible for the induction and maintenance of psoriatic plaques. Antibodies that inhibit IL‐12/23 or IL‐23 are key treatment options for patients with psoriasis. IL‐12 and IL‐23 also play a key role in immune responses to infections and tumors. A growing body of information from clinical trials, cohort studies, postmarketing reports, genetic studies and animal models provides insights into the potential biological relationships between IL‐12/23 inhibition and malignancies. We summarize this information in tables and provide some context for the interpretation of these data with the goal of informing dermatologists who are using IL‐12/23 or IL‐23 inhibitors to treat patients with psoriasis.